Too little, too late? Rice production to mitigate climate change in Colombia - Generale, Giovanni (2022)
Climate change has proven to threaten agriculture and food security (Shukla et al., 2019), negatively affecting the most vulnerable who crucially depend on agriculture for their own livelihood (Farauta et al., 2012). Acknowledging that poor production management practices exacerbate the problems and are responsible for low crop performance (Ajala et al., 2019) we evaluate if efforts to achieve climate-resilient and sustainable production have been too little or too late in the specific context of rice production in Colombia. In fact, since 2012, the Colombian Rice Producer Association (FEDEARROZ), the Colombian Ministerio de Desarrollo Rural, and Bioversity International and CIAT (formerly CIAT) have work to provide innovations focused on developing alternatives to reduce crop losses due to climatic factors. FEDEARROZ throughout their Massive Technology Adoption Program (AMTEC for its acronym in Spanish) has disseminated multiple of these innovations to support rice producers. This study evaluates how climate change impact on rice production can be mitigated by adopting practices and technologies disseminated by AMTEC. This is done analyzing the impact of adoption at the farmer level over several dimensions, such yield, carbon footprint, and production costs implementing an impact evaluation through propensity score matching. Using propensity-score marching models we found that adoption of technology contributed to the farmers adaptability to climate change showing higher yields and less carbon footprint. Indeed, the adopters experience an increase in yield of 580 kilograms per hectare and a decrease of 67 kilograms of greenhouse gasses emissions per ton produced.